Pembuatan Website Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan Kecamatan Pringkuku Kabupaten Pacitan - Winarsih, Sri; ,, Sukadi (Speed - Indonesian Journal on Computer Science, 2014)
Abstract: National Program for Community Empowerment Pringkuku Rural District is one of the establishments in the district Pringkuku to socialize and disseminate information about the program and its implementation to the community. in order to understand and be understood by the public especially as the perpetrators as well as the location of the target program beneficiaries. During this delivery and dissemination of information on program PNPM Rural District Pringkuku, only through liflet, bulletins, brochures and outreach through forums - discussion forums, workshops and other activities so that not all information can be known by the public. Dissemination of information may be more effective if the PNPM Rural District Pringkuku have a website as a medium to deliver information to the public .The benefit of this research is the establishment of a website that could facilitate the public in accessing information Pringkuku PNPM Rural District. Research methods used were observation, interviews, library research, design, testing and implementation. The expected outcome of the socialization process and the dissemination of this information is so that the results of the implementation of the program can be understood by the public. Keyword : PNPM MPd Website, Information Systems